2021
DOI: 10.1007/jhep10(2021)031
|View full text |Cite
|
Sign up to set email alerts
|

ModMax meets Susy

Abstract: We give a prescription for $$ \mathcal{N} $$ N = 1 supersymmetrization of any (four-dimensional) nonlinear electrodynamics theory with a Lagrangian density satisfying a convexity condition that we relate to semi-classical unitarity. We apply it to the one-parameter ModMax extension of Maxwell electrodynamics that preserves both electromagnetic duality and conformal invariance, and its Born-Infeld-like generalization, proving that duality invariance is preserved. We also estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…Note that study of duality invariant models, with and without supersymmetry, has a very long history. We refer the reader to the following (incomplete) list of papers and references therein [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Note that study of duality invariant models, with and without supersymmetry, has a very long history. We refer the reader to the following (incomplete) list of papers and references therein [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…I thank Dmitri Sorokin for kindly informing me of [54]. I am grateful to Stefan Theisen for a discussion, and to Michael Ponds and Emmanouil Raptakis for comments on the manuscript.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…6 A year ago, it was shown that there exists a unique model for conformal duality-invariant electrodynamics [52] (see also [53]). Recently its N = 1 superconformal extension has been introduced [54]. Below we will show how the N = 1 superconformal duality-invariant model of [54] naturally occurs within the framework developed in [8,16,43].…”
mentioning
confidence: 95%
See 2 more Smart Citations